Peripapillary retinal thickness and its risk factors in dry-type high myopia - Shanshan Li; Xiaohui Liu; Shuang Liu; Yiran Li; Yutong Ding; Min Yang; Dawei Zhang (Photodiagnosis and Photodynamic Therapy)
Introduction: To evaluate the alterations in the peripapillary retinal thickness and its risk factors in dry-type high myopia (HM). Methods: One hundred and twenty eyes in 69 HM subjects were collected from March 2023 to July 2023 with the age, refractive diopter, axial length (AL), posterior scleral staphyloma, type of myopic maculopathy, and peripapillary retinal thickness. Divided into three groups according to the international photo-graphic classification system: Category 0 (C0) with no myopic retinal degenerative lesions, Category 1 (C1) with tessellated fundus, and Category 2 (C2) with diffuse chorioretinal atrophy. Peripapillary retinal thickness was assessed using swept-source optical coherence tomography (SS-OCT) B-scans. All data were analyzed with the SPSS software version 23.0 by one-way ANOVA test among three groups. Linear regression and pearson correlation analysis were used to determine the relationships among measurements. Results: The retinal thickness of the peripapillary was measured from the superior, nasal, inferior, and temporal directions around the optic disc. The superior, nasal, and inferior peripapillary retinal thickness in the C2 group decreased significantly in all three groups. The retinal thicknesses decreased significantly with the increase of AL in the superior, nasal, and inferior. The retinal thicknesses increased significantly with the increase of refractive diopter, except for the temporal sector. The retinal thickness decreased significantly with the increase of age in dry-type HM. There was no significant difference between peripapillary retinal thickness and the wide macular staphyloma. Conclusions: Individuals in the C2 group had a thinner peripapillary retinal thickness than other groups, except for the temporal sector. The retinal thicknesses of the peripapillary decreased significantly with the increase of AL and increased significantly with the increase of refractive diopter, except for the temporal sector. With the increase of age, the retinal thickness of the peripapillary decreased significantly. Ophthalmologists and HM patients should pay attention to changes in the thickness of the peripapillary retina and the growth of age.